2018
DOI: 10.4067/s0034-98872018001201429
|View full text |Cite
|
Sign up to set email alerts
|

Association of maximal voluntary isometric handgrip strength with age, gender and handedness in older people

Abstract: Background: Maximal voluntary isometric handgrip strength (MVIHS) is influenced by age, sex, and handedness. Aim: To assess the association of MVIHS with age, sex, and handedness in older adults. Material and Methods: MVIHS was measured using a digital dynamometer in 60 men and 60 women aged 73 ± 6 years. Weight, height and handedness were also recorded. For analysis purposes, participants were divided into two age groups (65 to 70.9 years of age and ≥ 71 years). Results: A negative correlation was observed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Another consideration is that HGS evaluation should be carried out using calibrated dynamometers. Those belonging to the Jamar class are mainly used to evaluate HGS in clinical practice, as clearly emerged from the literature 30–44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another consideration is that HGS evaluation should be carried out using calibrated dynamometers. Those belonging to the Jamar class are mainly used to evaluate HGS in clinical practice, as clearly emerged from the literature 30–44 …”
Section: Discussionmentioning
confidence: 99%
“…Those belonging to the Jamar class are mainly used to evaluate HGS in clinical practice, as clearly emerged from the literature. [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] Eventually, we should make further reflections on HGS measurement modalities as an absolute value or correlating it to body weight. In this regard, two out of five studies included in the present review calculated HGS as a percentage of body weight.…”
Section: Comparing Measurement Methodsmentioning
confidence: 99%
“…For the measurement of the BCP, the Tanita ® BC-601 Bioimpedance Scale ISO 9001 Certified (Figure 1) was selected, which has eight reading electrodes. To evaluate the manual pressure force (MPF) we used the CAMRY EH101 dynamometer from General Asde S.A. (Valencia, Spain) (Figure 2) [38] and to evaluate the height of the countermovement jump (CMJ), we used MyJump2® App for smartphone. In all cases we used an iPhone 8 from Apple®.…”
Section: Methodsmentioning
confidence: 99%
“…HGS is a simple test with high reliability and validity to evaluate older people of all socioeconomic groups, nationalities, ethnicities, or cultural groups, which measures the strength exerted by the flexor–extensor muscles of the wrist [ 8 , 9 ]. A decreased HGS leads to a negative effect on functional independence [ 10 , 11 ] and has been associated with an increased risk of depressive symptoms, fall risk, frailty, hospitalizations, functional limitations, cognitive impairment, overweight/obesity, and considering the aspects listed, is related to minor life expectancy [ 4 ], promoting a reduced quality of life [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…While the relationship between HGS and the health status (i.e., nutritional status, functionality, depression, cognitive status, mortality) of older people is known [ 4 , 10 , 11 , 13 ], there is still no consensus on the effects of warming on HGS in older people [ 12 , 14 ]. For example, the study has shown that warm-up is intended to generate an increase in muscle temperature by facilitating increased blood flow, optimizing metabolic responses, reducing viscous muscle resistance (a smoother contraction) and increasing nerve transmission speed by seeking an optimal muscle temperature range that limits fatigue and maximizes performance [ 18 ].…”
Section: Introductionmentioning
confidence: 99%